Grain Refinement Assisted by Deformation Enhanced Precipitates through Thermomechanical Treatment of AA7055 Al Alloy - Jinrong Zuo; Longgang Hou; Xuedao Shu; Wenfei Peng; Anmin Yin; Jishan Zhang (Metals, 2020)
Fine-grained sheets of AA7055 Al alloy were produced by an improved double-stage rolling thermomechanical treatment (DRTMT) assisted by deformation-enhanced precipitates (DEPs). The DRTMT composed of a low temperature pre-deformation, an intermediate annealing, and a final hot rolling exhibited significantly superior tensile ductility to the conventional rolling thermomechanical treated alloy (CRTMT). Numerous fine spherical DEPs appeared after the pre-deformation. Those DEPs could exert a strong drag force on the migration of boundaries and dislocations. Dislocation cells were formed due to the drag force and dynamic recovery. These dislocation cells become polygon sub-grains by static recovery during the subsequent intermediate annealing. After the final hot deformation, with further deformation and rising temperature, low angle grain boundaries gradually stabilized and transferred to high angle grain boundaries. Due to the transformation, fine equiaxed grains were formed after DRTMT. The DRTMT alloys display superior elongation to the CRTMT alloy while maintaining high strength for grain refinement. Thus, DRTMT would be a good alternative to manufacture different heat-treatable Al alloys with fine grains efficiently.